Shape Optimization of Two-layer Acoustical Hoods Using an Artificial Immune Method - CHIU, Min-Chie (Archives of Acoustics, 2013)
Research on acoustical hoods used in industry has been widely discussed; however, the assessment ofshape optimization on space-constrained close-fitting acoustic hoods by adjusting design parameters hasbeen neglected. Moreover, the acoustical performance for a one-layer acoustic hood used in a high intensityenvironment seems to be insufficient. Therefore, an assessment of an optimally shaped acoustical hoodwith two layers will be proposed. In this paper, a numerical case for depressing the noise level of a pieceof equipment by optimally designing a shaped two-layer close-fitting acoustic hood under a constrainedspace will be introduced. Furthermore, to optimally search for a better designed set for the multi-layeracoustical hood, an artificial immune method (AIM) has been adopted as well. Consequently, this paperprovides a quick and effective method to reduce equipment noise by optimally designing a shaped multi-layer close-fitting acoustic hood via the AIM searching technique.